Time-course of neuroendocrine changes and its correlation with hypertension induced by ethanol consumption - da Silva, Andreia Lopes; Ruginsk, Silvia G.; Uchoa, Ernane Torres; Crestani, Carlos Cesar [UNESP]; Scopinho, America A.; Correa, Fernando Morgan A.; De Martinis, Bruno Spinosa; Elias, Lucila Leico Kagohara; Resstel, Leonardo B.; Antunes-Rodrigues, Jose (Oxford University Press (OUP), 2013)
Ethanol (ETOH) consumption has been associated with endocrine and autonomic changes, including the development of hypertension. However, the sequence of pathophysiological events underlying the emergence of this effect is poorly understood. Aims: This study aimed to establish a time-course correlation between neuroendocrine and cardiovascular changes contributing to the development of hypertension following ETOH consumption. Methods: Male adult Wistar rats were subjected to the intake of increasing ETOH concentrations in their drinking water (first week: 5%, second week: 10%, third and fourth weeks: 20% v/v). Results: ETOH consumption decreased plasma and urinary volumes, as well as body weight and fluid intake. Furthermore, plasma osmolality, plasma sodium and urinary osmolality were elevated in the ETOH-treated rats. ETOH intake also induced a progressive increase in the mean arterial pressure (MAP), without affecting heart rate. Initially, this increasein MAP was correlated with increased plasma concentrations of adrenaline and noradrenaline. After the second week of ETOH treatment, plasma catecholamines returned to basal levels, and incremental increases were observed in plasma concentrations of vasopressin (AVP) and angiotensin II (ANG II). Conversely, plasma oxytocin, atrial natriuretic peptide, prolactin and the hypothalamus-pituitary-adrenal axis components were not significantly altered by ETOH. Conclusions: Taken together, these results suggest that increased sympathetic activity may contribute to the early increase in MAP observed inETOHtreated rats. However, the maintenance of this effect may be predominantly regulated by the long-term increase in the secretion of other circulating factors, such as AVP and ANG II, the secretion of both hormones being stimulated by the ETOH-induced dehydration. © The Author 2013. Medical Council on Alcohol and Oxford University Press. All rights reserved.
Keywords: adrenalin; alcohol; angiotensin II; atrial natriuretic factor; catecholamine; noradrenalin; oxytocin; prolactin; sodium; vasopressin; adrenalin blood level; alcohol consumption; angiotensin blood level; animal experiment; animal model; animal tissue; body weight; catecholamine blood level; controlled study; disease association; disease course; fluid intake; heart rate; hypertension; hypothalamus hypophysis system; male; mean arterial pressure; neuroendocrine system; nonhuman; noradrenalin blood level; oxytocin blood level; plasma osmolality; plasma volume; priority journal; rat; sodium blood level; time; urine osmolality; urine volume; vasopressin blood level